Longer Poly(U) Stretches in the 3′UTR Are Essential for Replication of the Hepatitis C Virus Genotype 4a Clone in in vitro and in vivo - Takagi, Asako; Amako, Yutaka; Yamane, Daisuke; Kitab, Bouchra; Tokunaga, Yuko; El-Gohary, Ahmed; Kohara, Michinori; Tsukiyama-Kohara, Kyoko (Frontiers in Microbiology, 2021)
The 3′ untranslated region (UTR) of the hepatitis C virus (HCV) genome plays a significant role in replication including the poly(U) tract (You and Rice, 2008). Here we established an HCV clone that is infectious in vitro and in vivo, from an Egyptian patient with chronic HCV infection and hepatocellular carcinoma (HCC). First, we inoculated the patient plasma into a humanized chimeric mouse and passaged. We observed HCV genotype 4a propagation in the chimeric mouse sera at 1.7 × 107 copies/mL after 6 weeks. Next, we cloned the entire HCV sequence from the HCV-infected chimeric mouse sera using RT-PCR, and 5′ and 3′ RACE methodologies. We obtained first a shorter clone (HCV-G4 KM short, GenBank: AB795432.1), which contained 9,545 nucleotides with 341 nucleotides of the 5′UTR and 177 nucleotides of the 3′UTR, and this was frequently obtained for unknown reasons. We also obtained a longer clone by dividing the HCV genome into three fragments and the poly (U) sequences. We obtained a longer 3′UTR sequence than that of the HCV-G4 KM short clone, which contained 9,617 nucleotides. This longer clone possessed a 3′-UTR of 249 nucleotides (HCV-G4 KM long, GenBank: AB795432.2), because of a 71-nucleotide longer poly (U) stretch. The HCV-G4-KM long clone, but not the HCV-G4-KM short clone, could establish infection in human hepatoma HuH-7 cells. HCV RNAs carrying a nanoluciferase (NL) reporter were also constructed and higher replication activity was observed with G4-KM long-NL in vitro. Next, both short and long RNAs were intra-hepatically injected into humanized chimeric mice. Viral propagation was only observed for the chimeric mouse injected with the HCV-G4 KM long RNA in the sera after 21 days (1.64 × 106 copies/mL) and continued until 10 weeks post inoculation (wpi; 1.45–4.74 × 107 copies/mL). Moreover, sequencing of the HCV genome in mouse sera at 6 wpi revealed the sequence of the HCV-G4-KM long clone. Thus, the in vitro and in vivo results of this study indicate that the sequence of the HCV-G4-KM long RNA is that of an infectious clone.